Rap1b Association with the Platelet Cytoskeleton Occurs in the Absence of Glycoproteins IIb/IIIa - White, Gilbert C., II; Fischer, Thomas H.; Duffy, Christina M. (Thrombosis and Haemostasis, 1998)
Platelet membrane glycoproteins (GP) IIb/IIIa and rap1b, a 21 kDa GTP binding protein, associate with the triton-insoluble, activation-dependent platelet cytoskeleton with similar rates and divalent cation requirement. To examine the possibility that GPIIb/IIIa was required for rap1b association with the cytoskeleton, experiments were performed to determine if the two proteins were linked under various conditions. Chromatography of lysates from resting platelets on Sephacryl S-300 showed that GPIIb/IIIa and rap1b were well separated and distinct proteins. Immunoprecipitation of GPIIb/IIIa from lysates of resting platelets did not produce rap1b or other low molecular weight GTP binding proteins and immunoprecipitation of rap1b from lysates of resting platelets did not produce GPIIb/IIIa. Finally, rap1b was associated with the activation-dependent cytoskeleton of platelets from a patient with Glanzmann’s thrombasthenia who lacks surface expressed glycoproteins IIb and IIIa. Based on these findings, we conclude that no association between GPIIb/IIIa and rap1b is found in resting platelets and that rap1b association with the activation-dependent cytoskeleton is at least partly independent of GPIIb/IIIa.